Analisis Pengaruh Perdagangan Internasional dan Utang Luar Negeri Terhadap Gross Domestic Product Indonesia (Periode 1990 – 2010) - Ria Yani Fatmawati (Jurnal Ekonomi dan Studi Pembangunan, 2015)
The purposes of the study were to determine: (1) the short term effect of export, import, and external debt to the GDP of Indonesia years 1990 -2010, (2) the most dominant variable which affect to GDP of Indonesia years 1990–2010. The present study is explanatory research. The data were collection of the study is secondary data. Besides, the secondary data source of the study is taken from ADB (Asian Development Bank). Meanwhile, the data were collected through documentation. Based on the ECM, it is known that export affects positively and significantly to the GDP either long term or short term, import affects negatively and significantly to the GDP either long term or short term and external debt affect insignificantly to the GDP in a short term yet in a long term it affects negatively and significantly to GDP.Keywords: Stock Price, Capital Adequacy Ratio (CAR), Return on Assets (ROA), Loan to Deposit Ratio (LDR)